Systematic review and meta‐analysis of continuous local anaesthetic wound infiltration versus epidural analgesia for postoperative pain following abdominal surgery. Issue 10 (12th August 2013) - Ventham, N. T.; Hughes, M.; O'Neill, S.; Johns, N.; Brady, R. R.; Wigmore, S. J.
Abstract : Background: Local anaesthetic wound infiltration techniques reduce opiate requirements and pain scores. Wound catheters have been introduced to increase the duration of action of local anaesthetic by continuous infusion. The aim was to compare these infiltration techniques with the current standard of epidural analgesia . Methods: A meta‐analysis of randomized clinical trials (RCTs) evaluating wound infiltration versus epidural analgesia in abdominal surgery was performed. The primary outcome was pain score at rest after 24 h on a numerical rating scale. Secondary outcomes were pain scores at rest at 48 h, and on movement at 24 and 48 h, with subgroup analysis according to incision type and administration regimen (continuous versus bolus), opiate requirements, nausea and vomiting, urinary retention, catheter‐related complications and treatment failure . Results: Nine RCTs with a total of 505 patients were included. No differences in pain scores at rest 24 h after surgery were detected between epidural and wound infiltration. There were no significant differences in pain score at rest after 48 h, or on movement at 24 or 48 h after surgery. Epidural analgesia demonstrated a non‐significant a trend towards reduced pain scores on movement and reduced opiate requirements. There was a reduced incidence of urinary retention in the wound catheter group . Conclusion: Within a heterogeneous group of RCTs, use of local anaesthetic wound infiltration was associated with pain scores comparable to those obtained with epidural analgesia. Further procedure‐specific RCTs including broader measures of recovery are recommended to compare the overall efficacy of epidural and wound infiltration analgesic techniques . Abstract : Similar effect on short‐term pain relief